Exhibition - Strength in Numbers: The Polish Solidarity Movement - Until 2024-08 - Canadian Museum of Human Rights (Canadian Museum of Human Rights, 2023)
After decades of state oppression and denial of workplace rights, 16,000 workers at the Lenin Shipyard in Gdańsk, Poland, went on strike in 1980. Their protest erupted when labour activist Anna Walentynowicz was fired from her shipyard job. The mass strike action inspired the Solidarity movement that united 10 million workers and led to momentous political change. Strength in Numbers demonstrates the power of collective action during one of the largest labour uprisings in modern times.
Poland
Keywords: 2023-07 July; Poland; Solidarity Movement

Exhibition - Climate Justice - Until 2024-06 - Canadian Museum of Human Rights (Canadian Museum of Human Rights, 2023)
The exhibit “Climate Justice” highlights the connections between human rights and climate change, foregrounding youth activism and voices.
Worldwide
Keywords: 2023-07 July; Youth Activism